Israel : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Israel during 1990-94. During the first half of 1993, there was a significant slowing of the domestic economy largely as a result of a substantial scaling down of the public support provided to housing construction for immigrants, who were arriving to Israel in lesser numbers than originally estimated. In response to this slowing and to signs of a moderation in inflation, during the third quarter of 1993, the Bank of Israel reduced its lending rate from 12 percent to 9 percent in successive stages.